(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
In this study impact of injustice on work stress and counterproductive work behavior (CWB’s) was examined. The mediating role of work stress in the relationship of injustice and both active and passive CWB’s has been explored. Injustice contains three dimensional construct (distributive, procedural and interactional) while CWB’s were analyzed through production deviance as active CWB and withdrawal as passive CWB. Data were collected from 249 middle level managers from five different banks through a structured questionnaire. The purposed model was analyzed using Structural Equation Modeling (SEM) technique. Results revealed that all three dimensions of injustice have direct impact on work stress and indirect impact on production deviance and withdrawal behavior. Injustice creates stress and can have negative impact on behaviors of employees. Hence, employers should focus on providing justice not only for stress less work environment but also for positive behavior of employees.